Penalaran di balik prinsip-prinsip Outcomes-based Education dalam Merdeka Belajar - Janse Belandina Non; Rudi Susilana; Laksmi Dewi (Curricula: Journal of Curriculum Development, 2026)
Indonesia has implemented the Outcome-Based Education (OBE) approach through the Kurikulum Merdeka, which is based on learning outcomes, thereby promoting the concept of Merdeka Belajar. The OBE approach emphasizes direct experience for students as part of their learning process. This study aims to examine the implementation of an output-based curriculum and to discuss the rationale for the principles of OBE, outcomes-based curriculum, learning outcomes, and outcome-based assessment. This research uses a qualitative approach based on literature review methods, using the Directory of Open Access Journals (DOAJ) database. Data collected through information searches are then selected following inclusion and exclusion criteria. Furthermore, the selected data are analyzed using descriptive methods to detail the principles of OBE and the relationship between OBE and Merdeka Belajar, in relation to Carl Rogers's thinking on "freedom to learns". OBE emphasizes what can be achieved upon completion of learning and uses a learner-centered approach. The implementation of OBE is accompanied by an outcomes-based curriculum, outcomes-based learning and teaching, and outcomes-based quality improvement to measure student success or failure in learning outcomes. This aligns with Carl Rogers's philosophy, enabling students to learn with joy and a pleasant atmosphere, supported by the teacher's role as a facilitator.